The oil & gas engineering guide - Baron, Hervé (Editions Technip, 2010)
This book gives the reader an overview of how Oil & Gas Facilities are engineered. It covers their entire design cycle, from the high level functional duty to the detailed design. Each engineering task is described and illustrated with a sample document taken from a real project. Unlike engineering manuals which generally cover a specific discipline, such as process or civil engineering only, this work covers them all. Baron has done the hard work of distilling the essence of these disciplines and presenting them in a concise and precise fashion. Containing more than 250 illustrations, the book gives the reader a comprehensive information to easily refer to at any point in the project's life cycle. Contemporary engineering work for large projects is usually carried out at multiple locations. This does not make it easy for the new comer to gain an end-to-end knowledge. This work will fast track this acquisition. It will also meet the needs of anyone wishing to understand the technical factors driving the execution of a project -- Publisher's website.
Keywords: Petroleum engineering.; Gas engineering.; elektronické knihy; electronic books